RANCANG BANGUN SISTEM PEMANTAU KETINGGIAN AIR OTOMATIS MENGGUNAKAN SENSOR ULTRASONIK (HC-SR04) BERBASIS ARDUINO UNO DENGAN ANTARMUKA KOMPUTER BERBASIS MICROSOFT VISUAL BASIC 6.0 - Rizky Wahyu Pradana; Ganjar Febriyani Pratiwi; Tri Nur Arifin (Jurnal Teknik dan Science, 2024)
Efforts can be made to overcome this natural disaster, including providing a drainage system, maintaining forests and monitoring river water levels to determine the possibility of flooding if the level exceeds normal. In this research the author designed a tool to provide warnings before a flood disaster occurs. The design of an automatic water level monitoring system using an ultrasonic sensor (HC-SR04) based on Arduino UNO with a computer interface based on Microsoft Visual Basic 6.0 was created using HC-SR04 to measure distance, Arduino UNO as the main controller for the entire tool, LED and buzzer. When the HC-SR04 measures the distance by emitting waves from the trigger pin as the trigger and the echo pin as the receiver, the distance will then be processed by the Arduino UNO to calculate how many "cm" distances have been measured. If the distance calculated by the Arduino UNO is < 30 cm then the green LED will light up, if the distance is < 20 cm then the yellow LED will light up and the buzzer will sound slowly. However, if the distance is <10 cm, the red LED and yellow LED will light up alternately and the buzzer will sound loudly. Next, the data will be displayed on the PC interface with Microsoft Visual Basic 6.0 according to the distance received.